The Reality of Arms Trafficking in Algeria - Study in the Forbidden - Tazir, Amina (Journal of Legal Studies and Researches, 2020)
The Algerian legislator intervened with an arsenal of legal texts in order to put an end to the illegal use of weapons. The scholars considered this a positive step from the legislator in this regard, but nonetheless this legislative deterrent is still unable to put an end to the illegal use of weapons in Algeria, especially in terms of its trade, the latter constitutes the most dangerous form of dealing with weapons.